Politik Perubahan Penggunaan Lahan di Kalimantan Tengah: Lemahnya Tata Kelola yang Memicu Bencana Lingkungan - Puspita Ayu, Katriani (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2025)
The conversion of forest which occurred in Central Kalimantan was caused by the need for land expansion in the aim to meet the needs of food, infrastructure, and settlements. This study intends to identify how much forest has been converted into non-forest land, to point out the trend of increasing oil palm plantations, and spot the ecological impacts associated with land changes. The data described through a comparison of land use condition from 2014 to 2020 and take into account the condition of Central Kalimantan when it was hit by haze disaster in 2015 and 2019. The data shows that the decline in forest cover was followed by an increase in the expansion of oil palm plantations in the same timeframe. There was also an increase in the number of villages affected by the disaster in the same period of 2014 and 2018. Although the number of forest and land fires in 2019 was lower than in 2015, the data shows the distribution of hotspots which potentially trigger fires and haze remains high. In conclusion, land-use change is strongly correlated with the reduction of forest cover and the expansion of large-scale plantations. This situation is further exacerbated by documented cases of permit violations committed by plantation companies. Weak law enforcement and inconsistent policy implementation have also contributed to illegal land conversions, resulting in environmental degradation. There is an urgent need for environmentally oriented land-use management, supported by all stakeholders involved in land-use policy design, to ensure that such policies prioritize not only economic and political interests but also long-term ecosystem sustainability.